A View from Somewhere: Situating the Public Problem in Creative Writing Workshops - Erika Luckert (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
This essay is an effort to better situate the creative writing workshop in the diverse perspectives of its participants, by drawing on parallels between critiques of the writing workshop and critiques of the idealized public sphere. Habermas’s idealized public sphere has been critiqued for privileging dominant identities, much as creative writing workshops have been critiqued for privileging white writers like me. In this essay, I begin by listening to the critiques and testimony of BIPOC writers, which reveal that workshops are hegemonic spaces that reproduce and magnify racist, sexist, and classist systems. By reading these testimonies in conversation with critiques of the public sphere, I underscore the structural nature of this problem: when issues of race and culture are ignored in writing workshops, not only do we fail to achieve the ideal of an equitable space, we actively reinforce the power imbalances that we insist on overlooking. If, instead of trying to create a culturally neutral space, we welcome the complex identities of our students into our workshops, many parts of our pedagogy may need to change. To begin this work, I use Donna Haraway’s theory of situated knowledge to consider how we might workshop not with a pseudo-objective view, but with a “view from somewhere” instead. I suggest ways that author’s notes and workshop letters may be used to practice a more situated workshop, where participants reflect on their own positionings and learn to be accountable for the feedback they give.
Keywords: JAEPL